The baby-sitter burglaries - Keene, Carolyn; Copyright Paperback Collection (Library of Congress) (New York : Pocket Books, 1996)
Nancy tries to prove that a babysitter is being framed when three houses in River Heights are robbed and the only connection the police can find is that the babysitter was employed at each.
"A Minstrel book."
Keywords: Babysitters -- Fiction; Burglary -- Fiction; Young adult fiction